Investigation on Behavior of Elastoplastic Deformation for Ti–48Al–2Cr–2Nb Alloy by Micro‐Indentation and FEM‐Reverse Algorithm1 . Issue 8 (27th April 2017) - Yuan, Zhanwei; Wang, Chunwei; Li, Fuguo; Hu, Yongbiao; Guo, Yajie; Chen, Qi; Wang, Yingying; Guo, Mengle
Abstract : The Young's modulus, microhardness, and plastic properties of Ti–48Al–2Cr–2Nb alloy were determined using the micro‐indentation technique. Oliver–Pharr method was used to calculate Young's modulus and microhardness. The indentation load was inversely correlated to Young's modulus and microhardness. The decreased Young's modulus was associated with indentation damage, while decreasing hardness was due to indentation size effect. The plastic properties were determined using proposed FEM‐reverse algorithm, which combine finite element method and Matlab GA optimization tools. We used uniaxial compression test to verify the plastic properties calculated from the indentation tests, and it was found that the stress–strain plots predicted by FEM‐reverse algorithm was quite similar to the test results. Abstract : In this study, the mechanical properties of Ti–48Al–2Cr–2Nb are investigated by micro‐indentation experiments. A FEM‐reverse algorithm, which combined FEM simulation with Matlab GA optimization tools is proposed. And the FEM‐reverse algorithm has been verified with good prediction.